PM2.5 induce lifespan reduction, insulin/IGF-1 signaling pathway disruption and lipid metabolism disorder in Caenorhabditis elegans - Zhang, Wenjing; Li, Zinan; Li, Guojun; Kong, Ling; Jing, Haiming; Zhang, Nan; Ning, Junyu; Gao, Shan; Zhang, Yong; Wang, Xinyu; Tao, Jing (Frontiers in Public Health, 2023)
Exposure to fine particulate matter (PM), especially PM2.5, can induce various adverse effects on health, including diseases and premature death in populations. In the present study, water-soluble components of PM2.5 (WS-PM2.5) were collected in north China in winter, and combined in two groups with the final concentrations of 94 μg/mL (low concentration group, AQI ≤ 100) and 119 μg/mL (high concentration group, 100